Assessment of Spanish Panel Reactive Antibody Calculator and Potential Usefulness - Asensio, Esther; López-Hoyos, Marcos; Romón, Íñigo; Ontañón, Jesús; San Segundo, David (Frontiers in Immunology, 2017)
Background and objectives: The calculated panel reactive of antibodies (cPRA) necessary for kidney donor-pair exchange and highly-sensitized programs is estimated using different PRA calculators based on big enough samples in Eurotransplant (EUTR), United Network for Organ Sharing (UNOS) and Canadian Transplant Registry (CTR) websites. However, those calculators can vary depending on the ethnic they are applied. Here, we develop a PRA calculator used in the Spanish Program of Transplant Access for Highly Sensitized patients (PATHI) and validate it with EUTR, UNOS and CTR calculators. Methods: The anti-HLA antibody profile of 42 sensitized patients on waiting list was defined and cPRA was calculated with different PRA calculators. Results: Despite different allelic frequencies derived from population differences in donor panel from each calculator, no differences in cPRA between the four calculators were observed. The PATHI calculator includes anti-DQA1 antibody profiles in cPRA calculation; however, no improvement in total cPRA calculation of highly-sensitized patients was demonstrated. Interpretation and conclusions: The PATHI calculator provides cPRA results comparable with those from EUTR, UNOS and CTR calculators and serves as a tool to develop valid calculators in geographical and ethnic areas different from Europe, USA and Canada.